Pengaruh Kemampuan Mengakses dan Memahami Informasi Peserta KKN DR UIN Jakarta Terhadap Efikasi Diri Pencegahan Penyebaran Covid-19 di Masyarakat - Salshabilla Ayu Fortuna Wisudani; Muhammad Azwar (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: One activity that students usually do before the end of the semester is to participate in KKN (Real Work Lecture). In 2020 and 2021 UIN Jakarta conducted a KKN-DR (Real Work Lecture from Home) activity, which was a from adoption of KKN during the Covid-19 pandemic. The pandemic situation has made almost all human activities take place online, which of course requires the ability to access and understand good information.